Provenance and Geographic Spread of St. Louis Encephalitis Virus - Kopp, Anne (American Society of Microbiology, 2013)
St. Louis encephalitis virus (SLEV) is the prototypic mosquito-borne flavivirus in the Americas. Birds are its primary vertebrate hosts, but amplification in certain mammals has also been suggested. The place and time of SLEV emergence remain unknown. In an ecological investigation in a tropical rainforest in Palenque National Park, Mexico, we discovered an ancestral variant of SLEV in Culex nigripalpus mosquitoes. Those SLEV-Palenque strains form a highly distinct phylogenetic clade within the SLEV species. Cell culture studies of SLEV-Palenque versus epidemic SLEV (MSI-7) revealed no growth differences in insect cells but a clear inability of SLEV-Palenque to replicate in cells from birds, cotton rats, and free-tailed bats permissive for MSI-7 replication. Only cells from nonhuman primates and neotropical fruit bats were moderately permissive. Phylogeographic reconstruction identified the common ancestor of all epidemic SLEV strains to have existed in an area between southern Mexico and Panama ca. 330 years ago. Expansion of the epidemic lineage occurred in two waves, the first representing emergence near the area of origin and the second involving almost parallel appearances of the virus in the lower Mississippi and Amazon delta regions. Early diversification events overlapped human habitat invasion during the post-Columbian era. Several documented SLEV outbreaks, such as the 1964 Houston epidemic or the 1990 Tampa epidemic, were predated by the arrival of novel strains between 1 and 4 years before the outbreaks. Collectively, our data provide insight into the putative origins of SLEV, suggesting that virus emergence was driven by human invasion of primary rainforests.